Mechanically induced development and maturation of 3D in-vitro organoid platform: an organotypic heterogeneous microphysiological model of patient-derived organoids with ER/PR/HER2+ breast cancer - Kumari, Mamta; Alam, Kamare; Bhattacharya, Anamitra; Roy, Nakka Sharmila; Madhasu, Vaishnavi; Guchhait, Bitan; Dan, Sangita; Sett, Soma; Chakrabarti, Jayanta; Mandal, Chandan; Ravichandiran, Velayutham; Roy, Subhadeep (Frontiers in Immunology, 2025)
IntroductionBreast cancer comprises diverse histological and molecular subtypes, each characterized by distinct biological behaviors and therapeutic responses. So, to unravel the biological complexity of cancer tissue, we must research it down to the heterogeneous cell level, where one can investigate and deconstruct the molecular and biochemical characteristics of various cell types (Fibroblast, Endothelial Cells, and Cancer Stem cells). Unfortunately, advancements have been hindered due to the absence of thorough methods for identifying, isolating, and cultivating all patient-derived organoids (PDOs) types from various tissues. Personalized therapy in the form of PDOs represents a promising approach to advance therapeutic outcomes. This study aims to replicate the cellular and molecular heterogeneity of breast cancer by examining multiple cell types within PDOs and their contributions to tumor progression and metastasis.MethodsWe developed and characterized 3D in vitro PDO models from breast cancer tissues, encompassing various subtypes including ER+, PR+, and HER2+ tumors. We have sought to comprehend the fundamental nature of the various breast cancer cell types uncover the biology underlying their inherent characteristics, the outcomes of their interactions, and the contributions they provide to the metastatic potential. The IHC finding showed the positive expression for B cells (CD20), luminal epithelial cells (CD24), leukocytes infiltrating cells (CD45), mesenchymal stem cells (CD73, CD90, 105), vascular endothelial cells (CD34, CD105), EMT (E-cadherin), and fibroblast (Fibronectin, collagen, laminin) markers. In addition, we provide a new IHC/IF antibody panel and a stringent identification that can address significant breast cancer cells. Oxidative stress biomarkers and secretome analysis patterns were analyzed to identify the release pattern of variable pro-inflammatory growth cytokines produced by the endothelial and cancer stem cells.ResultsThe IHC finding showed the positive expression for B cells (CD20), luminal epithelial cells (CD24), leukocytes infiltrating cells (CD45), mesenchymal stem cells (CD73, CD90, 105), vascular endothelial cells (CD34, CD105), EMT (E-cadherin), and fibroblast (Fibronectin, collagen, laminin) markers. In addition, we provide a new IHC/IF antibody panel and a stringent identification that can address significant breast cancer cells. Oxidative stress biomarkers and secretome analysis patterns were analyzed to identify the release pattern of variable pro-inflammatory growth cytokines produced by the endothelial and cancer stem cells.DiscussionThe findings revealed the diverse fibroblast heterogeneity and variable epithelial to molecular profiles consistent with the original breast tumor. These 3D in vitro PDO models are essential for investigating the complex cellular interactions in breast cancer cells. This collection of research provides a fresh look at the model and serves as a valuable tool for developing tailored treatment strategies and facilitating personalized therapeutic approaches for breast cancer patients by illuminating its biochemical, cellular, and molecular make-up.